TTN novel splice variant in familial dilated cardiomyopathy and splice variants review: a case report - León, Paul; Franco, Paula; Hinojosa, Nicole; Torres, Kevin; Moreano, Andrés; Romero, Vanessa I. (Frontiers in Cardiovascular Medicine, 2024)
This case report details the identification of a novel likely pathogenic splicing variant in the TTN gene, associated with dilated cardiomyopathy (DCM), in a 42-year-old male patient presenting with early-onset heart failure and reduced ejection fraction. DCM is a nonischemic heart condition characterized by left biventricular dilation and systolic dysfunction, with approximately one-third of cases being familial and often linked to genetic mutations. The TTN gene, encoding the largest human protein essential for muscle contraction and sarcomere structure, is implicated in about 25% of DCM cases through mutations, especially truncating variants. Our investigation revealed a previously unreported G>C mutation at the splice acceptor site in intron 356 of TTN, confirmed by Sanger sequencing and not found in population databases, suggesting a novel contribution to the understanding of DCM etiology.The case emphasizes the critical role of the TTN gene in cardiac function and the genetic complexity underlying DCM. A comprehensive literature review highlighted the prevalence and significance of splice variants in the TTN gene, particularly those affecting the titin A-band, which is known for its role in muscle contraction and stability. This variant's identification underscores the importance of genetic screening in patients with DCM, offering insights into the disease's familial transmission and potential therapeutic targets.Our findings contribute to the expanding knowledge of genetic factors in DCM, demonstrating the necessity of integrating genetic diagnostics in cardiovascular medicine. This case supports the growing evidence linking splicing mutations in specific regions of the TTN gene to DCM development and underscores the importance of genetic counseling and testing in managing heart disease.